Theoretical-methodological differences diversifications and securities bank loan portfolio - O.V. Lysenok (Економіка, управління та адміністрування)
The article examines the essence of diversification as the main method of managing the credit activity of domestic banks, using which takes into account the ability of the loan portfolio to reduce the possible risk, when it includes different characteristics and composition of loans. The article also underlines that diversification can reduce not only credit risk, but also other banking risks that accompany the overall credit process: early repayment risk, liquidity risk, interest rate, currency risk and others. Traditional banking theory views diversification as the best way to effectively organize lending, with the most effective diversified lending activity. The article analyzes that the credit portfolio of Ukrainian banks is poorly diversified and very risky, as more than half of the loans granted by Ukrainian banks are concentrated in the Kyiv region and more than a third of the loans are in trade. The article clearly identifies the positive and negative aspects of diversification. The study of the securitization process shows that it is a relatively new type of banking for domestic banks. Due to the transformation of illiquid assets into liquid assets, securitization reduces the portfolio credit risk of a banking institution, which makes it possible to view securitization as a process of converting illiquid assets into securities, that is, one of the specific mechanisms for conducting financial and economic activities of banks. The article proposes to distinguish three main types of securitization: classic securitization, synthetic securitization, and business securitization. The article describes the reasons why Ukrainian banks are in no hurry to apply securitization, as well as its main advantages over asset diversification.